Physicochemical, exergetic and economical analyses of biogas reforming for hydrogen production - Souza, Antonio Carlos Caetano de; Silveira, José Luz (Revista Ciências Exatas, 2009)
The utilization of biogas for production of hydrogen-rich syngas through steam reforming and dry reforming is suggested in this study. Physicochemical analysis was performed with objective to evaluate the composition of syngas generated through reforming process. The adopted biogas in this study was based on the biogas generated in a small wastewater treatment system installed in São Paulo State University (UNESP) at Guaratinguetá. The volume of constituents was 61.8% CH4 and 34.4% CO2 after purification. The suggested thermodynamic conditions detected in physical-chemical and exergetic analysis was in a range of 600-900°C and 1 atm. Calculations of irreversibility, rational and exergetic efficiencies were developed. Basing on this analysis, the suggested conditions were 1 atm and maximum 700°C. Ultimately, an economic analysis was performed to evaluate the cost of produced hydrogen depending on of imposed conditions such as cost of installation of studied reformer system, operation, maintenance, and cost of biogas and carbon credits. The possibility to insert carbon credits was cited, since this biohydrogen production process contributes to diminish environmental impact.